Disseminated Histoplasmosis in an Elderly Man Presented with Fever, Weight loss, Abdominal Pain and Haemoptysis - A Case Report with Literature Review - Amin, Mohammad Robed; Shumi, Farzana; Khan, Hasibuddin; Abdullah, Syed Ahmed; Alam, Shafiul; Hussain, Ahmed Riyad; Kahhar, MA (Journal of Medicine, 2011)
An elderly patient presented with prolonged fever, gross weight loss, recurrent haemoptysis and abdominal pain. He had a background history of adrenal tuberculosis with completion of treatment without any obvious improvement. Clinically he was diagnosed as a case of adrenocotical insufficiency. Evaluation including histopathology revealed the diagnosis as disseminated histoplasmosis involving adrenal gland and lungs. The disease is a rarity without any underneath immunosuppression and hence high index of suspicion with appropriate steps for investigation is the key to achieve a diagnosis of disseminated histoplasmosis in Bangladesh. Keyword: . DOI: 10.3329/jom.v12i1.6936 J Medicine 2011; 12 : 81-85